CHILDFREE DAN RUANG PUBLIK: RESEPSI WARGANET TERHADAP PEREMPUAN CHILDFREE DALAM KOLOM KOMENTAR PADA KANAL YOUTUBE METRO TV NEWS - Nurul Ilmi Sudirman (Jurnal Komunikasi dan Media, 2024)
This study is motivated by the childfree choice for women which is now starting to become a new lifestyle among young Indonesian couples. This phenomenon is of course inversely proportional to the normative culture of Indonesian society, which expects married adults to have children. The childfree phenomenon then became a topic of conversation among netizens, especially in the YouTube comments space. This research aims to analyze and understand netizens' reception of childfree women in the video comment space entitled "Kick Andy- Childfree". Apart from that, to strengthen the role of the audience not only as consumers of media but also as producers of meaning. This research is located on the Metrotvnews Youtube channel which was uploaded on April 25 2022. Data sources are videos and comment transcripts which are analyzed using reception analysis. This research produced several findings that can be studied including; 1) Childfree choices and 'selfish choices' 2) Having children and social expectations 3) Childfree choices to 'enjoy the fruits of one's labor' 4) Women and a mother's 'natural instincts'. The findings show that there is a variety of acceptance of childfree women, ranging from comments that approve, praise, to reject. A message can be interpreted differently by netizens based on different sociocultural backgrounds, personal experiences, knowledge, religion and ethnicity. Even when decoders emphasize certain parts, they still make different readings. The presence of the YouTube comments space as a digital public space (public sphere) shows an increase in users' ability not only to express opinions, but to discuss and spark debate between users on controversial issues.